Preparation and characterization novel dioctyl terephthalate blended polyvinyl alcohol-composite films incorporated with the graphene oxide and silver nanoparticles - Ceran, Ozge Bildi; Simsek, Baris; Şara, Osman Nuri (Elsevier Sci Ltd, 2020)
Dioctyl terephthalate is of great interest as a replacement for the phthalate plasticizers such as dioctyl phthalate and diisononyl phthalate due to its orthophthalate-free and non-carcinogenic properties. This study focused on the production, characterization and optimization of the quality characteristics of its film properties, such as the mechanical, hydrophilic and thermal properties of dioctyl terephthalate-blended polyvinyl alcohol composites modified with graphene oxide and silver nanoparticles using TOPSIS (Technique for Order Preference by Similarity to an Ideal Solution) based Taguchi Method. Dioctyl terephthalate has brought remarkable features, such as high elastic modulus, and hydrophilic and thermal stability to the polyvinyl alcohol matrix. The optimum Dioctyl terephthalate -blended polyvinyl alcohol films have a 2.26 times lower contact angle and a 13.41 times higher elastic modulus than the reference polyvinyl alcohol film. Dioctyl terephthalate should be preferentially used to manufacture more durable and hydrophilic composite films such as fibers, disposable underpad or industrial swab, instead of toxic phthalate plasticizers.
Keywords: Graphene oxide; Polyvinyl alcohol-dioctyl terephthalate composite films; Hydrophilic; Silver nanoparticles; TOPSIS based taguchi method; Waste PET